Epidemiology of multidrug-resistant Gram-negative pathogens isolated from ventilator-associated pneumonia in ICU patients. (June 2017) - Gupta, Richa; Malik, Abida; Rizvi, Meher; Ahmed, Moied; Singh, Anuradha
Highlights: Ventilator-associated pneumonia (VAP) poses grave implications in endotracheally intubated ICU patients. Importance of antibiotic resistance among Gram-negative isolates in critically ill ICU patients. It is important to implement easy, discriminatory, reproducible and cost-effective detection of β-lactamase-producers. To overcome the problem of antibiotic resistance, it is necessary to reduce and optimise overall antibiotic consumption. The combined interaction of microbiologists, clinicians and the infection control team is needed. Abstract: Objectives: Antibiotic resistance among Gram-negative pathogens isolated from ventilator-associated pneumonia (VAP) poses a grave threat in intensive care unit (ICU) patients. The aim of this study was to assess the prevalence of pathogens in ICU patients and their drug resistance profile. The prevalence of extended-spectrum β-lactamases (ESBLs), AmpC β-lactamases and metallo-β-lactamases (MBLs) was also assessed. Methods: Tracheal aspirates were collected aseptically from 87 ICU patients between May 2012 and January 2014. Cultured isolates were identified by standard microbiological techniques. Antimicrobial susceptibility testing was performed according to Clinical and Laboratory Standards Institute (CLSI) guidelines. ESBLs and AmpC β-lactamases were detected both phenotypically and genotypically; MBLs were detected phenotypically. Results: A total of 77 isolate were cultured. Gram-negative bacteria comprised 68 (88.3%) of the total isolates, among which 49 (72.1%) were multidrug-resistant (MDR). Gram-positive organisms comprised four (5.2%) of the total isolates and all four (100%) were MDR. Aspergillus fumigatus (6.4%) was the only fungal pathogen identified. Conclusions: Pseudomonas aeruginosa was the predominant pathogen associated with VAP. The rising trend of antibiotic resistance in Gram-negative organisms is alarming. Regular monitoring of the pattern of resistance in ICUs is critical in effective management of VAP patients.